2015
DOI: 10.1155/2015/741687
|View full text |Cite
|
Sign up to set email alerts
|

Management of an Intruded Tooth and Adjacent Tooth Showing External Resorption as a Late Complication of Dental Injury: Three-Year Follow-Up

Abstract: Treatment and prognosis of intrusive luxation can vary depending on the age of the patient, type of dentition, stage of root development, and time and severity of the trauma. Some studies have demonstrated that intrusions of up to 3.0 mm have an excellent prognosis, whereas teeth with severe intrusion or teeth that are intruded more than 6.0 mm present an unfavorable prognosis because of the occurrence of inflammatory resorption and pulp necrosis. The aim of this case report is to present an 11-year-old male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, pulp necrosis and root resorption have been observed in adjacent teeth that were not directly impacted . It has been reported that even when the pulp response after trauma was positive, complications could develop after several weeks or months . These complications are frequently overlooked because they are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, pulp necrosis and root resorption have been observed in adjacent teeth that were not directly impacted . It has been reported that even when the pulp response after trauma was positive, complications could develop after several weeks or months . These complications are frequently overlooked because they are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…are described in the literature. 7 10 , 19 , 91 93 Risk factors include patient's gender, 9 age, 99 ethnicity, 84 , 85 root form, 83 , 106 occlusal peculiarities, 83 , 88 , 89 genetic predisposition, 14 16 , 83 , 86 , 87 underlying diseases. 101 , 103 , 105 The study of the above literature showed that there is no clear definition of etiological risk factors, all these factors either contribute or provoke the development of resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical factors occurring in orthodontic treatment (detailed description in the section of Orthodontic Treatment Mechanics Factors) can be a precondition to the development of root resorption, but these can be controlled and regulated to prevent complications. 83 , 90 Exogen factors include trauma, pulp infection, orthodontic treatment, tooth bleaching, etc.. 7 10 , 19 , 91 93 Thus, etiological and risk factors which can initiate or stimulate the development of resorption can be summed up as presented in Table 5 .…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations